Joint sink deployment and association for multi‐sink wireless camera networks. Issue 2 (19th August 2014) - Hung, Michael Chien‐Chun; Lin, Kate Ching‐Ju
Abstract: In this paper, we investigate the problem of joint sink deployment and association (JSDA) in multi‐sink wireless camera networks (WCNs). Each camera in a WCN requires a different streaming rate of delivering its stream back to an access point (sink) because of various surveillance requirements, for example, event detection or target tracking. In a WCN where multiple channels are supported, the sinks must be placed in suitable locations (sink deployment) to collect streams from cameras over nonoverlapping channels, and in addition, each camera must associate with the appropriate sink (sink association) so that its demand rate can be optimally satisfied. To achieve this goal, we first formulate the JSDA problem as an optimization model using mixed‐integer linear programming and prove its NP‐completeness. Two approaches, branch‐and‐bound and our heuristics, iterative sink deployment and association (ISDA), are then developed to solve JSDA. We evaluate the performance via simulations with the traces collected by real measurements and show that ISDA can effectively satisfy cameras' demands with a reasonable computational cost. Copyright © 2014 John Wiley & Sons, Ltd. Abstract : In a WCN, each camera requires a different streaming rate of delivering its stream back to sinks because of various surveillance requirements. Therefore, when multiple channels are supported, the sinks should be placed in suitable locations to collect streams from cameras over non‐overlapping channels. This paper investigates the problem of joint sink deployment and association in multi‐sink wireless camera networks.